THE IMPACT OF ELECTRONIC GOVERNANCE IN ENHANCING THE QUALITY OF ACCOUNTING INFORMATION (APPLIED STUDY IN KURDISTAN INTERNATIONAL BANK) - Hayder kareem salim (Scholar Express Journal, 2023)
The research aims to address the foundations of knowledge of electronic governance and indicate its importance and requirements for its application in banking units, in addition to explaining its role in accounting information with the quality required by internal and external users in order to rationalize their various administrative decisions in a manner that is commensurate with the variables of the contemporary business environment. The research was applied in one of the commercial banks listed in the Iraq Stock Exchange, which is the Kurdistan International Bank, for the period from 2011 to 2020 in order to demonstrate the role of electronic governance in improving the quality of accounting information and providing appropriate information for the needs of internal and external users. The research reached a set of conclusions, the most important of which was that electronic governance represents a new method for providing banking services to the customer with the aim of raising the efficiency of operational performance in the bank, reducing routine procedures that the customer suffers from, and providing information and data in an easy way to benefit from them in various decisionmaking. Electronic banking units can help improve the quality of accounting information.
Keywords: information; quality; external